“LOS COSTARICENSES NO HAN DEJADO DE ADMIRAR LAS MAGNIFICENCIAS DEL CIELO”: LA EVOLUCIÓN DE LAS IDEAS ASTRONÓMICAS EN COSTA RICA (1814-1910) - Díaz Bolaños, Ronald Eduardo (2005)
This work examines the extensive development of concepts on astronomy that occurred in Costa Rica throughout the XIX Century, as a result of research carried out by local and foreign scientists. In short, this work intends to analyze the processes that encouraged the development of these ideas in the country, with the opening of the first higher education institution (1814) up to the settlement of the greatest scientific dispute in relation to the passing of the Halley comet (1910).